Predicting immune checkpoint inhibitors response via fluorescence lifetime imaging microscopy: a systematic review - Cossa, Carlo; Frigato, Giulio; Lupo, Massimo; Mazzeo, Gabriele; Moro, Alex; Patrucco, Francesco; Wang, Reanna; Doni, Andrea; Colombo, Piergiuseppe (Frontiers in Immunology, 2025)
IntroductionFluorescence Lifetime Imaging Microscopy (FLIM) is an imaging technique that allows for the visualization of the cellular microenvironment by measuring the decay time of endogenous fluorescent molecules. Its advent has allowed the acquisition of information on previously undetectable aspects of the tissue environment, which also includes some mechanisms involving immune checkpoints. Understanding the level of interaction with their ligands is of paramount importance when stratifying patients for immunotherapy, as traditional methods such as immunohistochemistry (IHC) were found to be ineffective in predicting responders.MethodsThis review analyzes the current literature on FLIM as a means of predicting targets’ responsiveness to ICIs by examining the most relevant databases. Following PRISMA guidelines, we identified the relevant literature. The predefined objective of this review was to evaluate the potential of FLIM as a predictive biomarker of responsiveness to immune checkpoint inhibitors (ICIs). Eligibility criteria included original studies (clinical or preclinical) reporting on the use of FLIM to assess tumor or immune microenvironment in the context of ICI therapy. Reviews, case reports, editorials, and abstracts without full text were excluded.ResultsResearch suggests that interaction, not expression, is positively correlated with the effectiveness of ICI treatment. FLIM, in combination with FRET, allows for the quantification of the interactions within the tumor microenvironment.DiscussionThe scope of the review is to assist researchers in further exploring this technology for possible applications and for future drug interaction studies.